Study on corrosion cracking and oxidation mechanism of Inconel 718 burner of gasifier pulverized coal. (April 2020) - Wei, Yuwei Yw; Zhao, Qinxin Qx; Zhang, Xiaobin; Yang, Lili; Liang, Zhiyuan; Lai, Jiafeng; Zhong, Linzhi; Wang, Xiaolin
Highlights: Thermal fatigue crack propagation was due to the repeated start-up and shutdown of gasifier. Excessive δ phase weakens the matrix, and facilitates crack initiation and propagation. The distribution of elements at different depths of the corrosion oxide layer was described. Superalloys with better oxidation resistance should be selected. Abstract: The cracking mechanism of pulverized coal burner head of Inconel 718 gasifier was analyzed by means of macro-morphology examination, metallographic examination, scanning electron microscopy observation (SEM) and EDS analysis. The results show that the micro-cracks in the central hole of the burner intensify under the action of thermal stress, resulting in macro-cracks at the central hole of the burner head and oxidation corrosion layer on the surface during the repeated start-up and shut-down of the gasifier. Thermal fatigue and oxidation are the main causes of central cracking and surface oxidation of burner. Distribution and migration of elements such as Nb, Cr and Al during oxidation were studied.